THE EFFECT OF NPK AND ECO-ENZYME FERTILIZER APPLICATION ON THE GROWTH AND YIELD OF INPARI 32 VARIETY OF WELSHAW RICE - Nursamsidar; Muamar Kadafi; Musafir (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
The productivity of paddy fields in Indonesia still faces various obstacles, especially related to the decline in soil fertility due to the continuous use of inorganic fertilizers and the lack of optimal management of organic matter. Efforts to increase rice production need to be carried out through the application of fertilization technology that is able to improve soil conditions while increasing the efficiency of nutrient absorption. One alternative that can be applied is the combination of the use of NPK fertilizers and eco-enzymes in rice field cultivation. This study aims to analyze the effect of the application of NPK fertilizers and eco-enzymes on the growth and yield of rice fields of the INPARI 32 variety. The research was carried out in Boak Village, Moyo Hulu District, Sumbawa Regency, West Nusa Tenggara Province, from December 2025 to March 2026. The study was compiled using a Group Random Design (RAK) factorial pattern consisting of two factors. The first factor is the dose of NPK fertilizer which consists of three levels, namely P1 = 150 kg/ha, P2 = 300 kg/ha, and P3 = 450 kg/ha. The second factor is the concentration of eco-enzymes which consists of three levels, namely E1 = 10 ml/L of water, E2 = 20 ml/L of water, and E3 = 30 ml/L of water. Each treatment was repeated three times so that 27 experimental units were obtained. The observed parameters included plant height, number of seedlings, number of productive saplings, panicle length, grain weight per panicle, grain weight per clump, and weight of 1000 grains. The observation data were analyzed using multiple analysis (ANOVA) at a real level of 5% and continued with the Smallest Real Difference Test (BNT) at the level of 5% if the treatment showed a real effect. The results of the study showed that the application of NPK fertilizer had a real effect on plant height, number of productive saplings, panicle length, grain weight per clump, and weight of 1000 grains of rice field of INPARI 32 variety. NPK fertilizer treatment at a dose of 300 kg/ha (P2) provided the best response on most observation parameters. The application of eco-enzymes has a real effect on plant height and grain weight per clump, but it has no real effect on the number of productive saplings, panicle length, grain weight per panicle, and weight of 1000 grains. Eco-enzyme treatment with a concentration of 30 ml/L (E3) tends to produce better plant growth and yield than other treatments. In general, the combination of NPK fertilizer and eco-enzyme applications has the potential to increase the growth and yield of INPARI 32 rice fields through increasing the availability of nutrients and improving soil biological conditions.